Issue in Islamic equities: a literature survey - Masih, Mansur; Mustaffa Kamil, Nazrol Kamil; Bacha, Obiyathulla Ismath (Routledge Taylor & Francis, 2018)
This article reviews the current literature on Islamic equities. Our survey indicates that the bulk of articles is quantitative or empirical in nature, with a notable dearth of theoretical works. Among the common research themes explored by these articles are comparative performances of Islamic equities vis-à-vis their conventional counterparts, comparisons of Islamic portfolios with SRI funds, and empirically articulating portfolio diversification benefits associated with Islamic equities. In addition, numerous articles discuss idiosyncrasies of Shari’ah compliant stocks and portfolios under subthemes such as volatility, risk factors, and performance attributes. This survey also includes articles addressing efficiency perspectives, calendar anomalies, and issues in Shari’ah stock screening norms. We summarize general findings and offer suggestions for future research. Literature surveys on Islamic equities are few and far between, and this article, to date, represented the most recent and comprehensive attempt at that.